2017
DOI: 10.1002/2016jd026074
|View full text |Cite
|
Sign up to set email alerts
|

Urban emissions of water vapor in winter

Abstract: Elevated water vapor (H2Ov) mole fractions were occasionally observed downwind of Indianapolis, IN, and the Washington, D.C.‐Baltimore, MD, area during airborne mass balance experiments conducted during winter months between 2012 and 2015. On days when an urban H2Ov excess signal was observed, H2Ov emission estimates range between 1.6 × 104 and 1.7 × 105 kg s−1 and account for up to 8.4% of the total (background + urban excess) advected flow of atmospheric boundary layer H2Ov from the urban study sites. Estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 126 publications
2
20
0
Order By: Relevance
“…All observations presented in this work are 10‐s averages of the data collected at 1–2 Hz to improve the signal to noise ratio while maintaining temporal resolution. More information on the WINTER campaign and instrumentation can be found in papers published as a special collection (Guo et al, ; Salmon et al, ; Fibiger et al, ; Jaeglé et al, ; Haskins et al, ; Kenagy et al, ; Lee, Lopez‐Hilfiker, Schroder, et al, ; Lee, Lopez‐Hilfiker, Veres, et al, ; McDuffie, Fibiger, Dubé, Lopez Hilfiker, et al, ; McDuffie, Fibiger, Dubé, Lopez‐Hilfiker, et al, ; Ren et al, ; Salmon et al, ; Schroder et al, ; Sullivan et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…All observations presented in this work are 10‐s averages of the data collected at 1–2 Hz to improve the signal to noise ratio while maintaining temporal resolution. More information on the WINTER campaign and instrumentation can be found in papers published as a special collection (Guo et al, ; Salmon et al, ; Fibiger et al, ; Jaeglé et al, ; Haskins et al, ; Kenagy et al, ; Lee, Lopez‐Hilfiker, Schroder, et al, ; Lee, Lopez‐Hilfiker, Veres, et al, ; McDuffie, Fibiger, Dubé, Lopez Hilfiker, et al, ; McDuffie, Fibiger, Dubé, Lopez‐Hilfiker, et al, ; Ren et al, ; Salmon et al, ; Schroder et al, ; Sullivan et al, ).…”
Section: Methodsmentioning
confidence: 99%
“…The equipment on the Purdue Duchess aircraft included a global positioning system and inertial navigation system (GPS/INS), a Best Air Turbulence (BAT) probe for 3‐D wind measurements, a Picarro cavity ring‐down spectroscopy analyzer (Model G2301‐m) for CH 4 , CO 2 , and water vapor (H 2 O) measurements, and a Los Gatos Research Model RMT‐200 nitrogen dioxide (NO 2 ) analyzer based on cavity enhanced absorption spectroscopy. Further details about the instrumentation on the Duchess have been provided elsewhere (Salmon et al, , ).…”
Section: Experimental Description and Methodsmentioning
confidence: 99%
“…It is possible that there are some seasonal variations in CH 4 emissions from landfills and the estimated CH 4 emission rates in winter in this study may not be representative of other seasons. Ground-based studies have shown that CH 4 emissions from landfills are higher in winter than in summer mainly due to lower biological CH 4 oxidation in winter (Borjesson & Svensson, 1997;Christophersen et al, 2001;Rachor et al, 2013) and can be influenced by changes in barometric pressure, soil temperature, soil moisture, and wind (Lu & Kunz, 1981;Rachor et al, 2013;Xu et al, 2014;Young, 1992…”
Section: 1029/2018jd028851mentioning
confidence: 99%
“…Local-scale studies have examined the role of moisture source, condensation history, and land surface evapotranspiration on d-excess signatures (Benetti et al, 2014;Delattre et al, 2015;Griffis et al, 2016;Kelsey et al, 2018;Lai and Ehleringer, 2011;Uemura et al, 2008;Welp et al, 2012). Measurements of d excess in precipitation have been used to investigate below-cloud evaporation (Aemisegger et al, 2015;Froehlich et al, 2008;Wang et al, 2016) and mixing between the boundary layer (BL) and FT from stationary platforms near the surface or at high-altitude mountain sites (Bailey et al, 2015;Benetti et al, 2015;Froehlich et al, 2008;Galewsky, 2015;Lowenthal et al, 2016;Samuels-Crow et al, 2014). Kelsey et al (2018) conducted mobile traverses along leeward and windward slope roads of a mountain in an instrumented vehicle to report vertical profiles of d excess.…”
mentioning
confidence: 99%